1997
DOI: 10.2307/2953348
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Contraception: A National Survey of Adolescent Health Experts

Abstract: In a survey of 167 physicians with expertise in adolescent health, 84% said they prescribe contraception to adolescents, but only 80% of these prescribe emergency contraception, generally a few times a year at most. Some 12% of respondents said they believe that providing emergency contraception to adolescents would encourage contraceptive risk-taking, 25% said they think it would discourage correct use of other methods and 29% said they think repeated use of the method could post health risks. Physicians who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 25 publications
4
50
2
2
Order By: Relevance
“…The majority of these physicians, however, did not counsel their adolescent patients about EC during family planning visits. 36 In a case series of 1,076 consecutive sexual assault survivors presenting to a Denver ED, only 60% received EC. 37 A previous case series noted a similar figure.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these physicians, however, did not counsel their adolescent patients about EC during family planning visits. 36 In a case series of 1,076 consecutive sexual assault survivors presenting to a Denver ED, only 60% received EC. 37 A previous case series noted a similar figure.…”
Section: Discussionmentioning
confidence: 99%
“…Yet EC is underprescribed and underused in the United States. 1 Though the lack of awareness of EC is a barrier to wider use, 2 evidence indicates that physicians with good knowledge of the method routinely underprescribe EC, 3 whereas patients who know about EC often fail to use it when needed. 4 Furthermore, opinion surveys generally fi nd favorable views of the method among both physicians and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Few physicians educate patients about EC or assess need for EC during routine health or contraceptive-counseling visits. 3,10,11 Most prescribe EC on an emergency basis, when a patient requests it after an act of unprotected intercourse. In addition to preventing EC from reaching many patients who may not know enough about EC to ask for it, the emergency model constrains access in other ways.…”
Section: Introductionmentioning
confidence: 99%
“…Only 36% of respondents in a study were aware that anything "could be done "within a few days to prevent pregnancy, 55% "had heard" of emergency contraception and only 1% had used it [7]. A study of inner-city adolescents found that only 25% "had heard"of emergency contraception [8]. World wide, one of the biggest obstacles to the widespread use of emergency contraception is that many women do not know it [9].…”
Section: Introductionmentioning
confidence: 99%